Inhibitory Effect of Edible Additives on Collagenase Activity and Softening of Chilled Grass Carp Fillets. Issue 2 (4th July 2016) - Xu, Yanshun; Jiang, Xiaoqing; Ge, Lihong; Zang, Jinhong; Xia, Wenshui; Jiang, Qixing
Abstract: This study examined the inhibitory effects of catechin, tea polyphenols, gallic acid and Na‐citrate on the collagenase activity, collagen degradation and texture change of grass carp (Ctenopharyngodon idella) fillets over a period of 21 days under superchilling (−1.5C ± 0.2C) and ice storage (0.2C ± 0.1C) conditions. The results showed that catechin was the most effective inhibitor of collagenase activity, followed by tea polyphenol and gallic acid. Na‐citrate exhibited the lowest inhibitory effect on collagenase activity. All additives were able to suppress the softening of chilled fillets to varying degrees. Catechin effectively retarded the softening of grass carp fillets under both conditions. The firmness of chilled fillets treated with catechin were 72.6 (superchilling storage) and 75.8% (ice storage) higher than of the firmness of control fillets after 3 days of storage, respectively. However, treatments with Na‐citrate showed no obvious inhibitory effect on textural deterioration. Practical Applications: The texture of fillets when stored in chilled conditions inevitably deteriorated, represented by gapping and decreases in hardness. Recent studies have found that muscle softening is highly associated with collagen degradation induced by collagenase. Thus, the inhibition of collagenase and the stabilization of collagen are of great importance for controlling the autolytic degradation of fish muscle, thus alleviating the texture deterioration of chilled fillets. The inhibitory effect of four selected edible additives on the collagenase activity and texture deterioration of chilled grass carp fillets was investigated. Catechin effectively retarded the softening of chilled grass carp fillets. The present study provides a promising method for maintaining the texture quality of chilled fillet and extending the post‐mortem shelf‐life.